Multiple Invasions of Visitor, a DD41D Family of Tc1/mariner Transposons, throughout the Evolution of Vertebrates. (30th June 2020) - Shen, Dan; Gao, Bo; Miskey, Csaba; Chen, Cai; Sang, Yatong; Zong, Wencheng; Wang, Saisai; Wang, Yali; Wang, Xiaoyan; Ivics, Zoltán; Song, Chengyi
Abstract: Although the DD41D (named as Visitor, VS ) family of Tc1 / mariner transposons was discovered in Arthropods and Mollusca, the evolution profile of this family is still largely unknown. We found that VS is widespread in the animal kingdom, including 140 species of 18 orders in invertebrates and 30 species of 12 orders in vertebrates, and one land plant species. Our data revealed multiple horizontal transfer events in both invertebrates and vertebrates and invasion into multiple lineages of mammals, including Chiroptera (seven species), Dasyuromorphia/Marsupialia (one species), Didelphimorphia/Marsupialia (one species), Diprotodontia/Marsupialia (two species), and Primates (one species). Phylogenetic analysis revealed a close relationship of VS s to DD37D/ maT and DD34D/ mariner and confirmed that VS s with the DD40D signature identified previously are not a distinct family but originated from DD41D/ VS . Age analysis revealed that the most recent invasion of VS s was found in ray-finned fishes and a toad, followed by relatively young invasions in bats and marsupials, whereas VS s in mammals, jawless fishes, and lizards were mainly represented by ancient copies, suggesting old age. Phylogenetic analyses and comparison of pairwise distances between VS s and recombination-activating gene 1 ( RAG1 ) support horizontal transfer events of VS s in vertebrates. The intact VS s from bats were nonfunctional as determined by the transposition activity assay. Some vertebrate lineages and species were identified as the hot hosts of Tc1/mariner transposons. Overall, our study presents the evolution profile of VS s and suggests that VS s play roles in diversifying and shaping the genomes of diverse animal lineages.